A comparison of ant populations in restored forest of different ages and adjacent natural vegetation in Northern Thailand - Saowapa Sonthichai (2018)
The ant communities in restored forest 8, 6 and 4 years after planting with 30 native forest tree species (planted in 1997, 1999 and 2001 respectively) were compared with those of the adjacent natural vegetation in the north of Doi Suthep-Pui National Park, Chiang Mai Province, Thailand. A total of 1,486 ant specimens belonging to 6 subfamilies, 27 genera and 42 species were collected during 2003-2004. Four subfamilies of ants were recorded in all plots: Dolichoderinae, Formicinae, Myrmicinae and Ponerinae. Dorylinae and Leptanillinae were found only in the 8 year-old plots and in the natural vegetation, respectively. Ant population on the 4 year-old plot was highest. Succession of ants appeared to occur because populations decreases with increasing maturity of the forest plots. Ant communities in all plots were similar. Cluster analysis showed that the ant communities in the 8 year-old plots and the natural vegetation were most similar, followed by the 6 year-old plot. The community in the 4 year-old plot was considerably different from the others.